Analisis Pandangan Hakim Pengadilan Agama Tentang Hak Intervensi Anak dalam Proses Perceraian Orang Tuanya - Manurung, Farhan; Syahputra, Akmaludin (Nagari Law Review, 2024)
Parental divorce has the potential to affect children's rights, development and future stability. Children have curiosity and the right to a say in the division of family assets, yet their participation in divorce proceedings remains a challenge in the absence of a specific legal framework. This study aims to explore the views of Religious Court judges on children's intervention rights in parental divorce and ensure legal protection of these rights. The methodology used is a combination of qualitative legal analysis and empirical normative legal research. Primary data was obtained through interviews, while secondary data was collected through literature review. The results showed that there is no written regulation that explicitly regulates children's intervention rights in divorce proceedings. However, based on interviews with Religious Court judges, children who wish to provide testimony during divorce proceedings are allowed and legally recognized, as there are no prohibiting rules. This can be taken into consideration by the judge in deciding the case. However, to date there is no permanent framework, and implementation of children's intervention rights in Religious Court litigation procedures is minimal. Given that children are the most affected by divorce, it is important to establish a legal framework that protects their intervention rights to ensure children's needs and best interests are met.